An Analysis of Islamic Leadership Style at Ismart Ponorogo - Fajar Surya Ari Anggara; Muhammad Romzy Farras (Islamic Business and Management Journal, 2023)
Islamic leadership style is an interesting topic to discuss lately. This study aims to find out about how Islamic leadership is applied to Ismart. The several indicators used by the author in analyzing Islamic leadership at Ismart are honesty, trustworthiness, sincerity, good social skills, and wisdom. Researcher used a field research method with a qualitative approach. The sources interviewed by researcher are members of the Ismart organization, including one director of Ismart Ponorogo, two from the managerial team, one head of the shop and three employees of Ismart Ponorgo. The results of this study show that the Ismart leadership process has been implemented by Islamic values and teachings, supported by the implementation of RSC (Rules of Sharia Corporation).